2010
DOI: 10.1007/s13142-010-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing eHealth breast cancer interventions: which types of eHealth services are effective?

Abstract: Little is known about the effective elements of Interactive Cancer Communication Systems (ICCSs). A randomized trial explored which types of services of a multifaceted ICCS benefited patients and the nature of the benefit. Women with breast cancer (N=450) were randomized to different types of ICCS services or to a control condition that provided internet access. The Comprehensive Health Enhancement Support System (CHESS), served as the ICCS. ICCS services providing information and support, but not coaching suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(155 citation statements)
references
References 26 publications
2
150
0
3
Order By: Relevance
“…Internet only and Full CHESS conditions were shared by two studies. The CHESS breast cancer module is an Internet-based integrated eHealth system that provides patients and their families with a range of conceptually distinct services (See a detailed description of the original study from Baker et al, 2011; Hawkins et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Internet only and Full CHESS conditions were shared by two studies. The CHESS breast cancer module is an Internet-based integrated eHealth system that provides patients and their families with a range of conceptually distinct services (See a detailed description of the original study from Baker et al, 2011; Hawkins et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…To gauge the predictors of engagement types and their effects on patients’ outcomes, we decided to use the baseline survey, 6-week, and 3-month follow-ups only because (a) the original clinical trial demonstrated significant intervention effects primarily at 6-week or 3-month follow-up intervals (Baker et al, 2011), and (b) overall system usage after the 3-month follow-up was minimal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Gustafson et al [28] reported that the Comprehensive Health Enhancement Support System (CHESS) had a positive impact on QoL for women with breast cancer. CHESS was a computer-based program involving an information module, a communication module, and an interactive coaching module [14], which are, currently, easy to install and use through apps. Our BCS program indicated that the app-based BCS program could provide comparative functionality and achieve similar effectiveness as computer-based programs [28], while women could enjoy the advantage of convenience and easy access of apps.…”
Section: Principal Resultsmentioning
confidence: 99%
“…(T1) and 6 months (T2) of medical follow-ups with self-assessed paper questionnaires in the clinics. These time frames were chosen as greatest benefits of internet-based intervention were documented within 3 months [14], and some benefits might be sustained 6 months later The process of BCS development was published in Technology and Health Care [16]. Usercentric design were applied in BCS development and the perceived ease of using the BCS program was assessed [16].…”
Section: Study Design and Participantsmentioning
confidence: 99%